677 UTILITY OF 24 HOUR AMBULATORY BLOOD PRESSURE MONITORING (ABPM) IN PATIENTS WITH ORTHOSTATIC HYPOTENSION (OH) AT SYNCOPE CLINIC. (8th March 2022) - Arnott, A; Reid, G; Godwin, J; Anderton, L; Mitchell, L
Abstract: Introduction: OH is a disabling condition resulting from a sustained reduction in blood pressure (>20 systolic or 10 diastolic) within 3 minutes of standing. It is a common cause of syncope. Patients with concurrent hypertension experiencing syncope present a complex management dilemma where a balance must be established between symptom burden and risk of cardiovascular disease. Current guidance on ABPM use in syncope is limited. European society of cardiology syncope guidelines suggest ABPM in patients with 'autonomic failure' to assess nocturnal hypertension or drug-induced hypotension. Could this be improved with further explicit criteria on which patients to assess and how to act on results? The objective of this study is to review the use of 24 hour ABPM in OH within a tertiary referral syncope clinic. Method: A retrospective analysis was performed electronically for patients with a final diagnosis of OH seen in a syncope clinic between March 2017 and May 2019. Data was collected on comorbidities, medication history, physical mobility, clinic blood pressure, ABPM Results: (if performed) and medication changes. Comparisons were made between patients who had ABPM and those who did not. Statistics were calculated using Fisher's Exact Test (2 tailed). Results: 119 patients had a final diagnosis of OH in the study period. 45 had ABPM, 74 did not. The ABPM group had a significantly higher proportion of diagnosed hypertension (51.1% vs 23% (p = 0.0025)). A similar proportion of patients in both groups had medication changed however the ABPM group were significantly more likely to have antihypertensive therapy added (19.4% vs 1.8% (p = 0.0053)). Conclusion: Using 24 hour ABPM in OH patients can aid clinical decision making in the sub-group with hypertension. This can guide the need for alteration/addition of antihypertensive therapy to balance optimum BP control with symptom burden.